Analysis of the regulatory framework of foreign countries in terms of the functioning of securities markets as an integral part of ensuring its security (Economics and region, 2023)
This article conducts an in-depth analysis of the regulatory frameworks governing securities markets in foreign countries, emphasizing their role in ensuring market security and functionality. By examining the legislative frameworks of countries such as the United States and various European Union member states, the article aims to identify best practices that can be applied to enhance the regulatory environment of domestic securities markets. The study begins by exploring key regulations in the United States, such as the Sarbanes-Oxley Act of 2002, the Dodd-Frank Wall Street Reform and Consumer Protection Act of 2010, and the Jumpstart Our Business Startups Act of 2012. These laws introduce stricter compliance measures, define rules for financial document storage, enhance transparency, and promote accessibility for small businesses. Shifting focus to the European Union, the article examines the extensive regulatory landscape comprising directives and regulations such as the Markets in Financial Instruments Directive II, European market infrastructure regulation, and Prospectus Regulation. These regulations address transparency, accountability, investor protection, and standardization in areas ranging from trading practices to securitization and benchmarks. The article also highlights the significance of international organizations in shaping regulatory standards for securities markets, including the Group of 30, the International Organization of Securities Commissions, and the Association of European Central Securities Depositories. Their efforts in developing common standards and recommendations play a vital role in improving interaction among market participants, reducing risks, and enhancing the management of depository systems. Drawing from these analyses, the article presents valuable insights into the Ukrainian securities market. Recommendations are proposed to align domestic legislation with international standards, focusing on areas such as free float requirements, cooperation and information exchange, criminal liability, investor protection, diversification of investments, and the incorporation of state and self-regulatory approaches. By adopting and implementing foreign experience, the article asserts that a balanced and competitive securities market can be achieved. It underscores the importance of establishing a proper legal framework, ensuring compliance by issuers, investors, and regulatory bodies, and fostering collaboration among relevant stakeholders. In conclusion, this comprehensive analysis of foreign regulatory frameworks provides a roadmap for enhancing the regulatory environment of domestic securities markets. By embracing international best practices, policymakers and market participants can strengthen market security, improve functionality, and promote investor confidence, ultimately contributing to the long-term growth and stability of the securities market.
Keywords: securities market; directives; regulations; laws; standardization